Development of the Family Chronicle for Family Nursing Assessment - Hohashi, Naohiro; Horiguchi, Hanna; Watanabe, Mikio; Kawabata, Yoshino; Kijima, Natsumi (Rumah Jurnal, 2023)
Objective: The objective of this study was to develop the Chronological Table of the Plot of Family Story (PFS) as a new tool for assessment of the family chronicle, based the Concentric Sphere Family Environment Theory proposed by Hohashi. Method: Five researchers considered the PFS so as to enable use of the family chronicle, based on the records of family ethnography (family interviews/meetings, participant observation and others) conducted in Japan, China (Hong Kong), the Philippines and Indonesia and family case studies. Results: The four-page PFS consists of “a chronological table indicating the relationship and process of the plot of family story, family drama, family story, degree of family events, and condition of changes in the family (family signs/symptoms, family beliefs, family cognition/decisions/acts, etc.).” Conclusion: The PFS is an effective family nursing tool that can visibly indicate to what degree and in what manner the plot acts on family signs/symptoms.